Trait Dictionary Quality Control Tool version 1.0 and Documentation - Hazekamp, Thomas (Bioversity International and the International Center for Tropical Agriculture, 2021)
The Crop Ontology Guidelines provides recommendations about formats for Traits, Methods and Scales. The tool is an Excel-file which contains a number of macros to run tests on a Crop Ontology Trait Dictionary before upload in CO site. A description of the structure of the Excel-file and how to use it is provided in the “READ ME – Instructions”-sheet of the tool itself. A one-page user instructions if provided to support the use of the tool.